1998
DOI: 10.1182/blood.v92.9.3152.421a07_3152_3162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of BCL2, BCL6, and MYC Rearrangements in Diffuse Large B-Cell Lymphoma

Abstract: Diffuse large B-cell lymphoma (DLCL) is characterized by a marked degree of morphologic and clinical heterogeneity. We studied 156 patients with de novo DLCL for rearrangements of the BCL2, BCL6, and MYC oncogenes by Southern blot analysis and BCL2 protein expression. We related these data to the primary site of presentation, disease stage, and other clinical risk factors. Structural alterations of BCL2, BCL6, and MYC were detected in 25 of 156, 36 of 116, and 10 of 151 patients, respectively. Three cases show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
58
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 48 publications
8
58
0
4
Order By: Relevance
“…Kramer et al reported that 7 of the 10 patients with DLBCL with c-MYC had an extranodal lesion, and five of them were gastrointestinal tract lesions. (12) It is thought that their results are similar to those of the present report.…”
Section: Discussionsupporting
confidence: 92%
“…Kramer et al reported that 7 of the 10 patients with DLBCL with c-MYC had an extranodal lesion, and five of them were gastrointestinal tract lesions. (12) It is thought that their results are similar to those of the present report.…”
Section: Discussionsupporting
confidence: 92%
“…(D) Kaplan-Meier survival curve showing that the four variables, IPI ‡ 2, rearranged 3q27, > 50% BCL2 expression and lack of a GC phenotype, have an additive adverse prognostic effect. Each patient was ÔscoredÕ according to the presence or absence of each factor, giving scores of 0, 1, 2, 3 and 4. or no effect Pescarmona et al, 1997;Kramer et al, 1998;Vitolo et al, 1998). An explanation for the reported favourable outcome of patients with 3q27 rearrangements, in some studies, is the inclusion of significant numbers of patients with extranodal disease.…”
Section: Discussionmentioning
confidence: 97%
“…Primary extranodal DLBCL are, by definition, early stage, often localized, low-bulk tumours that are associated with a more favourable prognosis. BCL6 gene rearrangements are reported to occur more frequently in extranodal disease than in primary nodal disease Muramatsu et al, 1996Muramatsu et al, , 1997Liang et al, 1997a;Kramer et al, 1998), and inclusion of a significant number of extranodal lymphomas could mask the effect of the rearrangement on OS. In contrast, the present series consists entirely of a pure cohort of presentation cases of nodal DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations